No Clinically Relevant Effect of Heart Rate Increase and Heart Rate Recovery During Exercise on Cardiovascular Disease: A Mendelian Randomization Analysis - Mensah-Kane, Josephine; Schmidt, Amand F.; Hingorani, Aroon D.; Finan, Chris; Chen, Yutang; van Duijvenboden, Stefan; Orini, Michele; Lambiase, Pier D.; Tinker, Andrew; Marouli, Eirini; Munroe, Patricia B.; Ramírez, Julia (Frontiers in Genetics, 2021)
Background: Reduced heart rate (HR) increase (HRI), recovery (HRR) and higher resting HR are associated with cardiovascular (CV) disease, but causal inferences have not been deduced. We investigated causal effects of HRI, HRR and resting HR on CV risk, all-cause mortality (ACM), atrial fibrillation (AF), coronary artery disease (CAD) and ischemic stroke (IS) using Mendelian Randomization. Methods: 11 variants for HRI, 11 for HRR and two sets of 46 and 414 variants for resting HR were obtained from four genome-wide association studies (GWASs) on UK Biobank. We performed a look-up on GWASs for CV risk and ACM in UK Biobank (N = 375,367, 5.4% cases and N = 393,165, 4.4% cases, respectively). For CAD, AF and IS, we used publicly available summary statistics. We used a random effects inverse-variance weighted (IVW) method and sensitivity analyses to estimate causality. Results: IVW showed a nominally significant effect of HRI on CV events (odds ratio [OR] = 1.0012, P=4.11x10-2), and on CAD and AF. Regarding HRR, IVW was not significant for any outcome. The IVW method indicated statistically significant associations of resting HR with AF (OR = 0.9825, P=9.8x10-6), supported by all sensitivity analyses, and a nominally significant association with IS (OR = 0.9926, P=9.82x10-3). Conclusions: Our findings suggest no strong evidence of an association between HRI and HRR and any outcome, and confirm prior work reporting a highly significant effect of resting HR on AF. Future research is required to explore HRI and HRR associations further using more powerful predictors, when available.